Nanoemulsions and cyclodextrins inclusion complexes as methods of protection of essential oils for the development of bioherbicides - Vasconcelos, Loren Cristina; Mendes, Luiza Alves; Bergamin, Aline dos Santos; Martins, Geisiele Silva; Silva, Kaoany Ferreira da; Silva, Sonia Maria da; Fontes, Milene Miranda Praça (Seven Editora, 2023)
Essential oils are a source of promising bioactive compounds for the development of environmentally friendly herbicides. However, the low solubility, high volatility, and degradability make it impossible to apply essential oils under field conditions. Encapsulation in nanoemulsions and inclusion complexes can overcome these disadvantages by increasing the stability of these products. Recent studies have shown the ability of some protected essential oils to suppress weed development. This chapter reviews the processes of encapsulation and use of these essential oils. Inclusion complexes can be prepared using oligosaccharides such as cyclodextrins by the molecular inclusion method, while nanoemulsions can be obtained through low and high-energy methods. The development of nanoemulsions and inclusion complexes can increase the solubility and physicochemical stability of essential oils, providing stable formulations for use in agricultural fields. DOI:https://doi.org/10.56238/alookdevelopv1-137